2011
DOI: 10.2220/biomedres.32.181
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal administration of zingerol, a non-pungent analogue of zingerone, inhibits colonic motility in rats

Abstract: Zingerone, a pungent component of ginger, may exert beneficial therapeutic effects on hypermotilityinduced diarrhea because it has the ability to inhibit contractions of colonic smooth muscles. However, the pungency is undesirable for possible therapeutic use. The purpose of this study was to examine effects of zingerol, a non-pungent analogue of zingerone, in rats. Colonic motility in vivo was evaluated by measuring intraluminal pressure changes and expelled fluid volume from the colon in anesthetized rats. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…(Sharma and Gupta, 1998) In contrast, the ginger compounds zingerone and zingerol as well as whole ginger were reported to inhibit colonic motility in rats. (Iwami et al, 2011a;Iwami et al, 2011b) These diverse results indicate that ginger's effects could be a ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 10 result of the particular concentration of different bioactive compounds, or the synergy between them.…”
Section: Modulation Of Gastrointestinal Motility and Gastric Emptyingmentioning
confidence: 99%
“…(Sharma and Gupta, 1998) In contrast, the ginger compounds zingerone and zingerol as well as whole ginger were reported to inhibit colonic motility in rats. (Iwami et al, 2011a;Iwami et al, 2011b) These diverse results indicate that ginger's effects could be a ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 10 result of the particular concentration of different bioactive compounds, or the synergy between them.…”
Section: Modulation Of Gastrointestinal Motility and Gastric Emptyingmentioning
confidence: 99%
“…It was demonstrated that ginger accelerated gastric motility such as emptying and antral contractions in healthy volunteers and in patients with functional dyspepsia [12]. However about lower gastrointestinal region there are controversial reports [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In digestive tract, it has been demonstrated that ginger extract abolished the chemotherapy induced delay in gastric emptying in rats [16] and also it reduced nausea associated with motion sickness [17]. Moreover in rat colon it has been shown that ginger extract decrease motility [18]. While in the rat ileum it has spasmolytic effect [19], in guinea pig ileum ginger improves motility [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects were reversible and reproducible. As the pungency is undesirable in therapeutic use, an analogue of zingerone, zingerol was tested afterwards [112]. This compound had no inhibitory effect on the jejunum, inhibiting the contractile movements in isolated colonic segments only, suggesting it was directly acting on the colon.…”
Section: Gingermentioning
confidence: 99%